PENGARUH FINANCIAL DISTRESS, DISCLOSURE, PERKARA PENGADILAN DAN OPINI AUDIT TAHUN SEBELUMNYA TERHADAP PENERIMAAN OPINI AUDIT GOING CONCEN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2012-2015) - Ana Rahmawatul Faizah (e_Jurnal Ilmiah Riset Akuntansi, 2017)
A going concern audit opinion is a modified audit opinion given by the auditor if there is any doubt as to the viability of the enterprise within a reasonable period of time, not later than one year from the date the financial statements are being audited. Many cases of bankruptcy of the entity due to failure of auditors in assessing the company's ability to sustain its business motivate researchers to conduct this research. The purpose of this research is to analyze the influence of financial distress, disclosure, court case and audit opinion of previous year to going concern audit opinion on manufacturing company listed on BEI year 20122015. Methods in the sampling using purposive sampling and using logistic regression as a test tool research. The population used is manufacturing companies listed on the BEI 2012-2015. The sample of this research as many as 20 companies and due to menggunkan time span peneiltian 4 years then the number of samples there are 80 samples. The results of this study indicate that: (1) financial distress has a negative and significant effect on the going concern audit opinion, with a significance level of 0.017 <α 0.05. (2) disclosure has no significant effect on going concern audit opinion. With a significance level of 0.575> α 0.05. (3) the court case does not have a significant effect on going concern audit opoini, with a significance level of 0.977> α 0.05. (4) the previous year's audit opinion had no significant effect on going concern audit opinion, with significance level 0,796> α 0,05.